How a Dehumanising Form of Language Can Impact Outgroups' Decision to Engage in Violence: An Analysis of the Italian Far Left - Grillo, Giulia (PARTECIPAZIONE E CONFLITTO, 2025)
Despite considerable scholarship investigating engagement in violence, literature has overlooked how daily interpersonal relations and the use of a moralistic form of language impact individuals' decision to engage in violence. Presenting my research findings, this paper intends to bridge this gap by examining personal stories of a group of Italian former far-left militants, operating during the 'Years of Lead'. It employs narrative analysis, using Rosenberg's and Gilligan's perspectives on violent behaviour as theoretical lens. This paper identifies a three-step process, resulting from human cognition and partly implemented through a moralistic form of communication: firstly, employing Manichaean worldviews to make sense of society: secondly, the progressive dehumanisation of those falling into the negative side of these worldviews - outgroups; finally, outgroups' choice of engaging in violence. This paper finds that by promoting outgroups' dehumanisation, a form of language based on moralistic divisions significantly contributes to shaping outgroups' decision to engage in violence.